MELATIH METAKOGNISI SISWA DALAM MENUMBUH KEMBANGKAN EFIKASI DIRI (SELF-EFFICACY PADA PEMBELAJARAN MATEMATIKA - N. ERNI SUSIANI (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2021)
This study aims to find out how to train students' metacognition in developing self-efficacy in the Mathematics subject matter. The writing of this article uses a library research approach or literature study literature. Metacognition in general relates to how to explore one's thoughts about thinking. Self-efficacy is a form of belief or belief related to one's own ability to organize, do something to achieve a goal, produce something, and also implement actions in order to achieve a certain form of skill. Based on the literature study, training students' metacognition in developing self-efficacy in learning mathematics includes two dimensions of thinking, namely the awareness that a person has about his or her thinking (self-awareness of cognition) and a person's ability to use his/her consciousness to regulate his thinking process (self-regulation of cognition). By training to develop students' metacognitive awareness, it is expected that students can organize the information they face in solving problem-based questions so that they can develop students' mathematical self-efficacy.